Peculiarities of the clinical course of frederick’s syndrome on the background of comorbid pathology in the absence of adequate therapy - Hlavatskikh, Tatyana; Shop, Irina; Deriyenko, Tatiana; Kartvelishvili, Anna (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2020)
Atrial fibrillation in old people is one of the most common causes of cardiac decompensation. It can also lead to sudden cardiac death and thromboembolism of vital organs. Comorbidities such as diffuse cardiosclerosis, myocarditis or cardiomyopathy, congenital or acquired defects of the valvular apparatus of the heart, pathology of the endocrine system, chronic obstructive diseases of the bronchopulmonary apparatus, malignant course of arterial hypertension or its refractoriness to therapy, uncontrolled intake of antiarrhythmic drugs, can complicate the course of atrial fibrillation the addition of a transverse atrioventricular block, which is called Frederick’s syndrome. This article presents a case of clinical observation of an uncontrolled course of atrial fibrillation with the subsequent development and progression of severe circulatory failure against the background of the addition of complete atrioventricular block. Such an important factor as adherence to medical recommendations can compensate for various pathological conditions for a long time without causing significant harm to health, which was neglected by the patient from the clinical case under consideration. The launched course of arterial hypertension probably launched a cascade of morphological changes in the structures of the heart, which subsequently led to the formation of atrial fibrillation, the development of heart failure, and the addition of complete atrioventricular block. The appearance of rhythm in the heart rate, which is characteristic of this conduction disturbance, is often perceived as an erroneous restoration of the rhythm in case of pre-existing atrial fibrillation; this can complicate the timely diagnosis of pathology, especially in the absence of syncope conditions characteristic of complete atrioventricular blockade. The risks of thromboembolic complications and sudden cardiac death are as high as those associated with isolated atrial fibrillation. During the examination of the patient, the absolute indications for transplantation of an artificial pacemaker were determined. Subsequently, an increase in the minute volume of blood and cardiac output, as expected, led to an improvement in the clinical course of the disease and well-being, however, the pre-existing hemodynamic disorder of a long-term nature in this patient led to irreversible decompensation of cardiac activity, which adversely affects the long-term prognosis for life.